Feasibility Evaluation of a Microcontroller-Based SCADA Prototype as an Operational Traction Substation Monitoring System - Andri Pradipta; Amin Suharjono; Santi Triwijaya; Sunardi; Akhwan; Teguh Arifianto; Fadli Rozaq (Politeknik Perkeretaapian Indonesia Madiun, 2026)
This study evaluates the feasibility of a microcontroller-based Supervisory Control and Data Acquisition (SCADA) prototype for railway traction substation monitoring. A quantitative evaluative approach is employed using experimental data, focusing on reliability, response time, accuracy, and communication performance. The system integrates Arduino-based controllers, electrical sensors, TCP/IP communication, and a computer-based Human Machine Interface (HMI). Results show that the system achieves an operational success rate above 90% with an average response time below 2 seconds, indicating adequate performance for basic monitoring and control functions. However, compared to industrial SCADA standards, the system exhibits limitations in reliability, security, and scalability. Therefore, the prototype is classified as having limited feasibility, suitable for educational and simulation purposes but not for direct operational deployment. This study provides a structured evaluation framework and highlights key gaps for future development of more robust SCADA systems. This study contributes by introducing a quantitative feasibility evaluation framework for low-cost SCADA systems in railway applications.